2015
DOI: 10.15386/cjmed-437
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Three-dimensional Sonographic Assessment of the Embryonic Brain: A Pilot Study

Abstract: AimsA very good knowledge of human embryology is mandatory not only for the correct sonographic assessment of the developing brain, but also for better understanding the origins of congenital anomalies involving the central nervous system. 3D transvaginal sonography may be an effective technique for imaging the developing brain. The aims of this explorative study are to demonstrate the feasibility of imaging the embryonic brain between 7 and 10 weeks of gestation for clinical studies by using a 3D high-frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…While some scholars have reported that the cerebellum and the 4th VCP can be seen at 8 weeks of menstrual age, 19,20 Boitor-Borza et alfound that only the metencephalon and the myelencephalon were visible at 8 weeks (with a CRL of 17 mm). 17 The novel finding of this study is that the orientation of the 4th VCP appears to change from being perpendicular to the long axis of the neural tube to being parallel to it in fetuses measuring 41-84 mm CRL, as observed from the mid-sagittal view. This discovery is in agreement with the embryological images published by Bayer and other embryologists, 12 indicating that the high-resolution ultrasound imaging findings correlated well with the anatomy of solid specimens.…”
Section: Correlation Between the Crl And Vermis Circumferencementioning
confidence: 56%
See 3 more Smart Citations
“…While some scholars have reported that the cerebellum and the 4th VCP can be seen at 8 weeks of menstrual age, 19,20 Boitor-Borza et alfound that only the metencephalon and the myelencephalon were visible at 8 weeks (with a CRL of 17 mm). 17 The novel finding of this study is that the orientation of the 4th VCP appears to change from being perpendicular to the long axis of the neural tube to being parallel to it in fetuses measuring 41-84 mm CRL, as observed from the mid-sagittal view. This discovery is in agreement with the embryological images published by Bayer and other embryologists, 12 indicating that the high-resolution ultrasound imaging findings correlated well with the anatomy of solid specimens.…”
Section: Correlation Between the Crl And Vermis Circumferencementioning
confidence: 56%
“…utilized the OmniView software and reported that embryos with a CRL of 9 mm only exhibit a relatively simple anatomical brain structure. Specifically, they were only able to identify the forebrain, midbrain, and rhombencephalon 17 . In our study, we discovered that using high‐resolution transvaginal 3D sonography, the structure of the prosencephalon, mesencephalon, and rhombencephalon can be clearly visualized in embryos with a CRL of 10–15 mm.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations